2020
DOI: 10.1111/coa.13544
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteatoma and family history: An international survey

Abstract: ObjectiveTo explore the relative frequency of a family history of cholesteatoma in patients with known cholesteatoma, and whether bilateral disease or earlier diagnosis is more likely in those with a family history. Associations between cleft lip or palate and bilateral disease and age of diagnosis were also explored.DesignAn online survey of patients with diagnosed cholesteatoma was conducted between October 2017 and April 2019.ParticipantsThe sample consisted of patients recruited from two UK clinics and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In the NL family, PID III-2 was diagnosed with cholesteatoma at 17 years of age. β-catenin (part of WNT pathway) expression is increased in cholesteatoma cells when compared with normal epithelium cells and we postulate that cholesteatoma, like otosclerosis, may be a result of mutation in FOXL1, given reported cases of familial cholesteatoma, including rare autosomal dominant families (Collins et al 2020;Jennings et al 2018). Industry focus on pharmacologically modulating the Wnt signalling pathway in cancer provides a potential treatment option for otosclerosis and possibly cholesteatoma as well (Zimmerli et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the NL family, PID III-2 was diagnosed with cholesteatoma at 17 years of age. β-catenin (part of WNT pathway) expression is increased in cholesteatoma cells when compared with normal epithelium cells and we postulate that cholesteatoma, like otosclerosis, may be a result of mutation in FOXL1, given reported cases of familial cholesteatoma, including rare autosomal dominant families (Collins et al 2020;Jennings et al 2018). Industry focus on pharmacologically modulating the Wnt signalling pathway in cancer provides a potential treatment option for otosclerosis and possibly cholesteatoma as well (Zimmerli et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the NL family, PID III-2 was diagnosed with cholesteatoma at 17 years of age. β-catenin (part of WNT pathway) expression is increased in cholesteatoma cells when compared with normal epithelium cells and we postulate that cholesteatoma, like otosclerosis, may be a result of mutation in FOXL1, given reported cases of familial cholesteatoma, including rare autosomal dominant families (Collins et al 2020;Jennings et al 2018). Industry focus on pharmacologically modulating the Wnt signalling pathway in cancer provides a potential treatment option for otosclerosis and possibly cholesteatoma as well (Zimmerli et al 2017).…”
Section: Discussionmentioning
confidence: 92%
“…A clinical observation of familial clustering, and the possibility of a heritable component for cholesteatoma was reported by one of the authors in 2009 (18). A systematic review on the genetics of cholesteatoma identified 35 relevant studies, including case-reports describing segregation of cholesteatoma within families in a pattern consistent with a monogenic, oligogenic, or multifactorial trait (19), and in a recent survey more than ten percent of cholesteatoma patients reported a positive family history (20). Identifying functionally important gene variants associated with disease has potential to uncover the molecular basis of cholesteatoma pathology, and whole exome sequencing (WES) can identify variants in coding DNA that co-segregate with the phenotype.…”
Section: Background and Rationale For The Studymentioning
confidence: 99%
“…A clinical observation of familial clustering, and the possibility of a heritable component for cholesteatoma was reported by one of the authors in 2009 (18). A systematic review on the genetics of cholesteatoma identified 35 relevant studies, including casereports describing segregation of cholesteatoma within families in a pattern consistent with a monogenic, oligogenic, or multifactorial trait (19), and in a recent survey more than ten percent of cholesteatoma patients reported a positive family history (20).…”
mentioning
confidence: 99%